Study of the Package Degradation of IGBT Module during Thermal Cycling Test - XU Ninghua; PENG Yongdian; LUO Haihui; FENG Huiyu; LI Liangxing; LI Han (Kongzhi Yu Xinxi Jishu)
Failure mechanisms of IGBT module are complex, one of which is package degradation. To eliminate the interference of application condition and other effects, the correlation between module failure and package degradation was built via severe thermal cycling test. Results show that the degradation will be encountered after packaging, such as solder layer delamination, loose busbars and lift-off bonding wires, which may cause module failure. Principle of material selection and structure design was get by studying the theory of material mechanics. The influence of packaging process was discussed and the optimized methods were proposed aiming to solder layer and bow of baseplate, IMC, terminal soldering, wire bonding, etc.